PERAN KOMISI PEMILIHAN UMUM DAERAH (KPUD) JAKARTA UTARA DALAM MEWUJUDKAN TINGGINYA PRESENTASE PARTISIPASI POLITIK MASYARAKAT DISABILITAS DI WILAYAH JAKARTA UTARA PADA PEMILU SERENTAK 2019 - Anggraeni Ekasuci Lestari, (2023)
This study aims to find out the role of the North Jakarta KPUD in the high percentage of disabled voter turnout in the North Jakarta area and how the experiences of persons with disabilities in North Jakarta are regarding the implementation of the 2019 simultaneous elections. The research method used in this research is a Qualitative research with explanatory research using primary data and secondary data. The premier data collection technique used is the In-Depth Interview Method and is supported by secondary data sources through documentation, reports and attachments to related regulations and laws. The qualitative data analysis process used by researchers is based on Miles & Huberman's analysis stages, which consist of data collection, data reduction, data presentation, and conclusion/verification. Based on the results of this study it is known that in carrying out its role, socialization efforts are carried out by the North Jakarta KPUD to increase the participation of disabled voters in North Jakarta through Inclusive Political Socialization by involving Disabled Groups and also targeting the Beginner Voter Segmentation with Disabilities in efforts to increase the political participation of disabled voters carried out by the North Jakarta KPUD by carrying out face-to-face socialization through channels of disability organization groups and special schools to provide political education about the implementation of the 2019 simultaneous elections. In addition, North Jakarta KPUD's efforts to increase the participation of disabled voters are also through accessibility and information services provided given to voters with disabilities.